Geometry of the hemispherical radiometric footprint over plant canopies - B. Marcolla; A. Cescatti (Theoretical and Applied Climatology, 2018)

Convergence of potential net ecosystem production among contrasting C 3 grasslands - Matthias Peichl; Oliver Sonnentag; Georg Wohlfahrt; Lawrence B. Flanagan; Dennis D. Baldocchi; Gerard Kiely; Marta Galvagno; Damiano Gianelle; Barbara Marcolla; Casimiro Pio; Mirco Migliavacca; Michael B. Jones; et al. (Ecology Letters, 2013)
Metabolic theory and body size constraints on biomass production and decomposition suggest that differences in the intrinsic potential net ecosystem production ( NEP POT ) should be small among contrasting C 3 grasslands and therefore unable to explain the wide range in the annual apparent net ecosystem production ( NEP APP ) reported by previous studies. We estimated NEP POT for nine C 3 grasslands under contrasting climate and management regimes using multiyear eddy covariance data. NEP POT converged within a narrow range, suggesting little difference in the net carbon dioxide uptake capacity among C 3 grasslands. Our results indicate a unique feature of C 3 grasslands compared with other terrestrial ecosystems and suggest a state of stability in NEP POT due to tightly coupled production and respiration processes. Consequently, the annual NEP APP of C 3 grasslands is primarily a function of seasonal and short‐term environmental and management constraints, and therefore especially susceptible to changes in future climate patterns and associated adaptation of management practices.

Ecosystem carbon fluxes and canopy spectral reflectance of a mountain meadow - D. Gianelle; L. Vescovo; B. Marcolla; G. Manca; A. Cescatti (International Journal of Remote Sensing, 2009)

Comparing CO2 Storage and Advection Conditions at Night at Different Carboeuroflux Sites - M. Aubinet; P. Berbigier; Ch. Bernhofer; A. Cescatti; C. Feigenwinter; A. Granier; Th. Grünwald; K. Havrankova; B. Heinesch; B. Longdoz; B. Marcolla; L. Montagnani; et al. (Boundary-Layer Meteorology, 2005)

Quality analysis applied on eddy covariance measurements at complex forest sites using footprint modelling - C. Rebmann; M. Göckede; T. Foken; M. Aubinet; M. Aurela; P. Berbigier; C. Bernhofer; N. Buchmann; A. Carrara; A. Cescatti; R. Ceulemans; R. Clement; et al. (Theoretical and Applied Climatology, 2005)

Canopy Architecture and Turbulence Structure in a Coniferous Forest - B. Marcolla; A. Pitacco; A. Cescatti (Boundary-Layer Meteorology, 2003)